Peroxisomal ether-glycerophospholipid synthesis is dysregulated after TBI - Amir A. Mehrabani-Tabari; Nivedita Hegdekar; Sabrina Bustos; Yulemni Morel; Yuanyuan Ji; Sazia Arefin Kachi; Olivia Pettyjohn-Robin; Sagarina Thapa; Maya Bhattiprolu; Marta M. Lipinski; Jace W. Jones; Chinmoy Sarkar (Journal of Lipid Research)
Ether-glycerophospholipids (ether-GPs), the ether bond- (– O –) containing glycerophospholipids, are major components of the brain lipidome. Ether-GPs play a crucial role in regulating neuronal function, and their deficiency has been implicated in many neurodegenerative diseases. However, how they are affected after traumatic brain injury (TBI) is not known. Our data demonstrate a significant decrease in ether-GPs abundance in the mouse cortex following controlled cortical impact (CCI)-induced TBI. This is at least in part due to the impairment of peroxisomal ether-GP synthesis in the mouse brain after TBI. We detected dysregulation of peroxisomal ether-GPs synthesizing enzymes – glyceronephosphate-O-acyltransferase (GNPAT) and alkylglycerone phosphate synthase (AGPS) in the injured mouse brains. Our data demonstrate a significant decline in GNPAT level in the peroxisomal fraction and a marked accumulation of AGPS in the cytosol of mouse cortices after TBI. To restore the ether-GP level in the injured brain, we treated TBI mice with an ether-GP precursor, 1-O-octadecylglycerol (OAG), to bypass the peroxisomal ether-GPs synthesizing steps. OAG partially restored the levels of several ether-GPs, attenuated inflammatory cytokine expression, and improved their functional recovery after TBI. Taken together, our data demonstrate that the decline in ether-GPs abundance after TBI is at least in part due to the impairment in peroxisomal ether-GPs synthesis and that restoration of ether-GPs by OAG treatment can improve TBI outcomes.